Factors impacting antimicrobial resistance in the South East Asian food system and potential places to intervene: A participatory, one health study - Lambraki, Irene Anna; Chadag, Mohan Vishnumurthy; Cousins, Melanie; Graells, Tiscar; Léger, Anaïs; Henriksson, Patrik John Gustav; Troell, Max Fredrik; Harbarth, Stephan; Wernli, Didier; Jørgensen, Peter Søgaard; Carson, Carolee Anne; Parmley, Elizabeth Jane; et al. (Frontiers in Microbiology, 2023)
Background With AMU projected to increase, South East Asia (SEA) is at high risk of experiencing disproportionate health, social, and economic burdens due to antimicrobial resistance (AMR). Our objective was to identify factors influencing AMR in SEA’s food system and places for intervention by integrating the perspectives of experts from the region to inform policy and management decisions. Material and Methods We conducted two 6.5 hour workshops and two 90-minute interviews involving 18 AMR and other disciplinary experts from human, animal and environment sectors who brainstormed the factors influencing AMR and identified leverage points (places) for intervention. Transcripts and workshop materials were coded for factors and their connections and transcribed into a causal loop diagram (CLD). Thematic analysis described AMR dynamics in SEA’s food system and leverage points for intervention. The CLD and themes were confirmed via participant feedback. Results Participants constructed a CLD of AMR in the SEA food system that contained 98 factors interlinked by 362 connections. CLD factors reflected eight sub-areas of the SEA food system (e.g., government). Seven themes (e.g., antimicrobial and pesticide use and AMR spread (n=40 quotes)), six ‘overarching factors’ that impact the entire AMR system (e.g., the drive to survive (n=12 quotes)), and ten places for intervention that target CLD factors (n=5) and overarching factors (n=2) emerged from workshop discussions. Conclusions The participant derived CLD of factors influencing AMR in the SEA food system demonstrates that AMR is a product of numerous interlinked actions taken across the One Health spectrum and that finding solutions is no simple task. Developing the model enabled the identification of potentially promising leverage points across human, animal and environment sectors that, if comprehensively targeted using multi-pronged interventions, could evoke system wide changes that mitigate AMR. Even targeting some leverage points for intervention, such as increasing investments in research and capacity building, and setting and enforcing regulations to control antimicrobial supply, demand and use could, in turn, shift mindsets that lead to changes in more difficult to alter leverage points, such as redefining the profit-driven intent that drives system behavior in ways that transform AMU and sustainably mitigate AMR.